Factors Associated with African-American Women’s Decisions to Participate in Genetic Research - Still, Carolyn H. (J Natl Black Nurses Assoc, 2014)
The purpose of this study was to determine the factors that are associated with African-American (AA) women’s decisions to participate in genetic research. Using a descriptive correlational design, a convenience sample of African-American women (age ≥ 40) was recruited from various locations in the Midwest. During semi-structured interviews, demographics, psychological factors, knowledge of and attitudes toward genetics were collected. Of the 98 women (mean age 53), 66% indicated that they were unwilling to participate, despite having positive attitudes. Correlations were found between genetic knowledge and attitudes toward genetics (r = .35, p = .001), and decision-making to participate and attitudes toward genetics (r = .40, p = .001). Data revealed decisions were largely associated with their lack of knowledge and resulting perceptions. Efforts should be made to inform African-American women about the benefits of the new science through planned, culturally specific, and sensitive interventions that incorporate genetic and health literacy programs.